Analisis Kemiripan Unsur Desain Pada Karakter Spider-Man Dengan Karya Digital Artificial Intelligence - Muhammad Adi Sukma Nalendra; Dinda Okta Dwiyanti Ridwan Gucci; Alfajar Madani (Besaung : Jurnal Seni Desain dan Budaya, 2025)
Character design aims to convey a strong visual and personality identity, as exemplified by successful industry characters such as Spider-Man. The strong identity of Spider-Man has inspired extensive responses in the form of digital art design, including the boundless realm of AI-generated art. The phenomenon of AI’s openness on social media raises questions about the authenticity of designs produced by AI, particularly works featuring Spider-Man as a popular design. Ultimately, within the scope of Visual Communication Design studies, comparing original versus AI-generated Spider-Man character designs through Manga Matrix analysis becomes essential to understand which elements are retained and which distinguish the authenticity of the Intellectual Property’s visual characteristics. This research employs a descriptive qualitative approach using Manga Matrix analysis and focus group discussions (FGD). The results show that similarities in several Manga Matrix elements within AI works indicate that the character still refers to the original Intellectual Property. Conversely, the Personality aspect tends to disappear when the Intellectual Property’s visual elements are modified, resulting in differences from the original visual elements. This research may contribute design recommendations for designers by indicating that Personality aspects can change if the visual elements that compose them are modified by AI